Cellular Plasticity in Prostate Cancer Bone Metastasis. (3rd June 2015) - Jadaan, Dima Y.; Jadaan, Mutaz M.; McCabe, John P.
Abstract : Purpose. Experimental data suggest that tumour cells can reversibly transition between epithelial and mesenchymal states (EMT and MET), a phenomenon known as cellular plasticity. The aim of this review was to appraise the clinical evidence for the role of cellular plasticity in prostate cancer (PC) bone metastasis. Methods. An electronic search was performed using PubMed for studies that have examined the differential expression of epithelial, mesenchymal, and stem cell markers in human PC bone metastasis tissues. Results. The review included nineteen studies. More than 60% of the studies used ≤20 bone metastasis samples, and there were several sources of heterogeneity between studies. Overall, most stem cell markers analysed, except for CXCR4, were positively expressed in bone metastasis tissues, while the expression of EMT and MET markers was heterogeneous between and within samples. Several EMT and stemness markers that are involved in osteomimicry, such as Notch, Met receptor, and Wnt/ β pathway, were highly expressed in bone metastases. Conclusions. Clinical findings support the role of cellular plasticity in PC bone metastasis and suggest that epithelial and mesenchymal states cannot be taken in isolation when targeting PC bone metastasis. The paper also highlights several challenges in the clinical detection of cellular plasticity.